Different Seasonal Precipitation Anomaly Patterns in Central Asia Associated With Two Types of El Niño During 1891–2016 - Feng, Fan; Zhao, Yong; Huang, Anning; Li, Yang; Zhou, Xin (Frontiers in Earth Science, 2022)
In this study, we examine the different seasonal precipitation anomaly patterns in Central Asia associated with the cold-tongue (CT) El Niño and warm-pool (WP) El Niño from the El Niño developing summer to the decaying summer based on the Global Precipitation Climatology Centre (GPCC) full data reanalysis version 7 (GPCC V7) data set. Overall, El Niño are associated with more precipitations over Central Asia, but significant discrepancies can be found in the precipitation anomaly spatial patterns associated with the two types of El Niño from the El Niño peaking winter to the decaying summer. More precipitation can be seen in southwestern Central Asia during the peaking season of CT El Niño; while during the peak season of WP El Niño, more precipitation occurs in southern Central Asia. In the spring after the peaking season, the impact of CT El Niño on anomalous precipitation is mainly concentrated in the belted area on both sides of 45ºN over Central Asia, while WP El Niño causes the increase of precipitation over almost the whole area of Central Asia. During the El Niño decaying summer, the influence of CT El Niño on precipitation anomalies in Central Asia is significantly reduced in extent, while for WP El Niño, there is still a large range of positive precipitation anomalies in northeastern and middle Central Asia. Possible physical mechanics for the differences are discussed using ERA5 reanalysis data. The anomalous rising branch of the equatorial Indian Ocean , the formation and diminution of the anomalous high pressure north of Central Asia and the southward and northward movements of anomalous high pressure south of Central Asia at different stages of the two types of El Niño affect the rising motion over Central Asia and the southwestward and northward water vapor flux transport, resulting in the spatial pattern of precipitation anomalies in Central Asia corresponding to the different developing stages of the two types of El Niño.